HUBUNGAN ANTARA PENGGUNAAN CELEBRITY ENDORSER PADA IKLAN BEAUTY PRODUCT DENGAN PEMBENTUKAN BODY IMAGE KONSUMEN REMAJA PEREMPUAN - Susan Mintaraga (Universitas Trunojoyo Madura, 2015)
Adolescent have a sense of dissatisfaction and have lessof the confidence in them body image. Adolescent use their ways to transform their appearance that considered unsatisfying. Beauty products is one of alternative for adolescent to improve them look, like a skin care, hair care, nail care, and make up. Currently, beauty products become one of the need and must be met by adolescent, especially young girls. The needs for the beauty products be used as by companies to develop their businesses. The company trying to attract the attention of consumers, so that the adolescent are increasingly interested to using beauty products. Advertising is the one of techniques in the promotional marketing. With the advertising, company can introduce, promotion, persuade, and give the information the product to consumer (the adolescent, especially young girls). In the advertising, use of celebrity endorseris expected toattract more consumers to buy the dangusing beauty products. In addition to attract customers, the use of celebrity endorser in advertisements can change consumer behavior toward body image among girls has. Appearence attractive celebrity endorsea shaving a perfect body shape, a beautiful face, and white skin causing consumer desire to becomes like their idols, even they will make every effort to have the appearance and use whatever is used by celebrity endorser.